Intercultural Learning Critical preparation for international student travel - Jones, Peter (UTS ePRESS, 2019)
The ability to recognise and understand your own cultural context is a prerequisite to understanding and interacting with people from different cultural backgrounds. An intercultural learning approach encourages us to develop an understanding of culture and cultural difference, through reflecting on our own context and experience.